KEY DIRECTIONS FOR RISK MANAGEMENT IMPROVEMENT (European Journal of Economics, Finance and Business Development, 2026)
This article examines the key directions for improving risk management systems in modern financial and corporate environments. The increasing complexity of global economic relations, digital transformation, and financial market volatility require organizations and financial institutions to develop more effective risk management frameworks. The research analyzes international practices in risk management, particularly focusing on developed economies, and evaluates the current state of risk management implementation in Uzbekistan. The study identifies the main challenges affecting risk management efficiency, including technological risks, regulatory challenges, and organizational barriers. Through comparative analysis and statistical review, the article highlights the importance of integrated risk management strategies, digital tools, and institutional reforms. The findings indicate that organizations adopting advanced risk governance structures demonstrate higher resilience and financial sustainability. The article concludes with practical recommendations aimed at strengthening risk management systems through improved regulatory frameworks, adoption of modern analytical technologies, and enhanced professional training. The results may contribute to improving decision‑making processes and strengthening financial stability at both institutional and national levels.